2021
DOI: 10.1021/acs.jmedchem.1c00532
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Optimization of Potent and Orally Bioavailable Purine Scaffold as a Dual Inhibitor of Toll-Like Receptors 7 and 9

Abstract: Several toll-like receptors (TLRs) reside inside endosomes of specific immune cellsamong them, aberrant activation of TLR7 and TLR9 is implicated in myriad contexts of autoimmune diseases, making them promising therapeutic targets. However, small-molecule TLR7 and TLR9 antagonists are not yet available for clinical use. We illustrate here the importance of C2, C6, and N9 substitutions in the purine scaffold for antagonism to TLR7 and TLR9 through structure–activity relationship studies using cellular reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…The conceptual design of the compounds was influenced by our previous experience with the essential structural features and geometrical arrangements in different chemotypes such as benzoxazole, , oxoadenine, imidazoquinoline, quinazoline, and other cores. To identify the minimal substitutions required to attain TLR7/9 antagonism, initially, 7–11 were prepared with small substituents at the C4′ and C2′ positions. The C2′ substitution was to impart obvious geometrical restrictions in the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conceptual design of the compounds was influenced by our previous experience with the essential structural features and geometrical arrangements in different chemotypes such as benzoxazole, , oxoadenine, imidazoquinoline, quinazoline, and other cores. To identify the minimal substitutions required to attain TLR7/9 antagonism, initially, 7–11 were prepared with small substituents at the C4′ and C2′ positions. The C2′ substitution was to impart obvious geometrical restrictions in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Sequential incorporation of relevant structural subunits in a basic molecular framework of imidazopyridine at C7, C3, C2, and C2′ positions provided compounds 13 , 16 , 22 , 25 , 26 , 36 , 37 , and 41 as the prospective lead candidate. To further optimize these lead candidates we evaluated them in a panel of in vitro ADME assays (Tables and ). ,,, These compounds have different substitutions at C7, C3, and C2′ positions. Thus, this would provide an understanding of the correlation between in vitro pharmacokinetic properties and different structural modifications in the imidazopyridine scaffold for lead selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ( +)-naltrexone [( +)-NTX], an antagonist of TLR2 and TLR4, was effective at treating MS-related memory deficits with both lower- and higher-dose in EAE mice but failed to alleviate EAE-induced motor deficits [ 148 ]. TLR7/9 antagonists, compound 29 and IRS-954 (immunoregulatory DNA sequence-954), showed therapeutic efficacy in a preclinical murine model of psoriasis and lupus, respectively [ 149 , 150 ]. Wang et al found that total coumarins from Urtica dentata Hand could prevent murine autoimmune diabetes by suppressing the TLR4 signaling pathways in DCs [ 151 ].…”
Section: Inhibitors Targeting Innate Receptorsmentioning
confidence: 99%
“…The antimalarial agent hydroxychloroquine (HCQ), which operates as a nonselective endosomal TLR inhibitor, is widely utilized in the treatment of various autoimmune disorders [28]. Various researchers have reported molecules with quinazoline [29,30], benzoxazole [31][32][33], imidazopyridine [34,35], purine [36][37][38], and other varied scaffolds [39,40] that have been significantly investigated for the development of selective small-molecule TLR7 antagonists in several recent studies through empirical screenings and activity-guided strategies.…”
Section: Introductionmentioning
confidence: 99%